AB0418 Effectiveness of Rituximab as First and Second Line Therapy in Patients with Rheumatoid Arthritis. (9th June 2015) - Mahmoud, I.; Jradi, S.; Saidane, O.; Rekik, S.; Sahli, H.; Elleuch, M.; Tekaya, R.; Abdelmoula, L.
Abstract : Background: The order of use of biologic agents after failing a TNF inhibitor is still a question for debate. Recent clinical practice guidelines recommend the use of Rituximab after previous failure of one anti-TNF. Objectives: This study aims to compare the efficacy of first and second line of Rituximab and factors associated with, in patients with rheumatoid arthritis (RA). Methods: Retrospective analysis of 40 Tunisian RA database was included. RA patients initiating a first line either anti-TNF (adalimumab (ADA), etanercept (ETA) or infliximab (INF)) or Rituximab (RTX) were identified and followed forward in time. Anti TNF was then switched with Rituximab, which has become the second line. Baseline demographics included age, disease duration, fatigue and pain visual analogical scale evaluations (VAS) and DAS 28 ESR. The therapeutic efficacy was assessed on the EULAR response criteria. Results: The analyzed cohort comprised patients with average age of 53, 85 years (80% female). 21 patients initiating a first line anti TNF (ADA (n=2), ETA (n=7), INF (n=10), ETA then ADA in one case and INF then ETA in another one case). The evolution marked by a primary therapy failure in 6 cases and a secondary therapy failure in 8 cases. Anti TNF was then switched to RTX. The reason for the switch was therapy failure (n=12) and adverse effects (n=8). In this group, the EULAR response criteria were positive in 57% (Good in 6 cases and moderate in 6 cases). For patients (n=19) who have started in a first line RTX, the EULAR response criteria were positive in 94% (Good in 8 cases and moderate in 10 cases). Seven patients had positive antinuclear antibodies whose 57% had positive EULAR response criteria (Good in 1 case and moderate in 3 cases) and whose 3 patients were under second line RTX therapy who have not developed therapy response. Total, 75% of patients developed positive EULAR response criteria under RTX, whose 50% were under Methotrexate, 43% received more than one course of RTX whose 53% maintained therapeutic efficacy at week 16. Conclusions: As a first line agent, RTX demonstrates a better retention rate than in second line. Disclosure of Interest: None declared